AUTOMATIC FLOODS ALERTING SYSTEM USING GSM & PC - Karthikeyan.K; Mrs.K.P.Jamunalaksmi (International Journal of Advance Engineering and Research Development (IJAERD), 2018)
The purpose of a flood warning service is to detect and forecast threatening flood events so that the public can be alerted in advance and can undertake appropriate responses to minimise the impact of the event. This is a particularly important technology in developing countries, where flooding results in massive loss of life and property. Flood warnings are a highly important adaptive measure where protection through large scale, hard defences, is not desirable or possible. This may be the case if defences would cause adverse environmental or social problems, or where the cost of defence construction would be prohibitive. The project is to provide the sensor automatic Flood alerting system. Monitoring of water level, rain flow checking and Water flow velocity by the sensors. River water level and rain flow and water velocity status is monitored by the sensors and transfer to GSM and Computer. For easy surveying and with less delay the information can be send to the authority. To avoid flood based accident and to safeguard the people.